The Role of Volunteers in German Refugee Crisis and their Contribution to the Local Government Expenditure - Chang Woon Nam; Peter Steinhoff (Center for Economic Studies and ifo Institute (CESifo), 2018)
This study deals with a specific volunteering aspect revealed in the German refugee crisis 2015/16. German federalism prescribing interjurisdictional assignments of tasks for designing, financing and implementing services for refugees and their geographic distribution have made municipalities and cities primarily responsible for solving problems of refugees' accommodation, integration and health care. Based on a survey recently carried out in the district of Erding, it firstly demonstrates distinctive characteristics of the individual volunteers engaged in such related local activities (gender and age; income structure; donation types; working hours), followed by an attempt to measure economic values of volunteering. Despite some methodological weaknesses, this study highlights the monetary significance of volunteers' hidden contribution to overcoming the crisis and the relatively huge scope of possible savings in local expenditure, compared to an assumed situation if such voluntary activities were fully substituted by those of full-time civil servants.
Keywords: D64; D91; E65; H72; 330; volunteer activity; German refugee crisis; economic value of volunteering; local government expenditure; district of Erding